PERAN PENYULUHAN DALAM PEMBERDAYAAN PETANI KELAPA SAWIT POLA SWADAYA DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Sigit, Ibnu; Yulida, Roza; ', Rosnita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research are: (1) To identify the role of extension on independent small holder farmers of oilpalm; (2) To know empowerment level of the farmers; (3) To analyze the purpose of extension; (4) To analyze influence the role of extension toward empowerment and influence empowerment toward the extensionpurposes. This research was conducted at Harapan BaruVillage and Sebangar Village in Mandau Sub District Bengkalis District. Research’s respondent was determined by purposive sampling methods with number of respondent were 125. The consideration to choose the location is the location that has active extension activities and has farmer group. Validity, reliability, outliers, normality and multicolinearity analysis has been done on the measuring instruments. To answer the first, second, and third purpose of this research using likert’s scale summated rating (SLR). To answer the fourth research purpose was using structural equation modeling (SEM) with the AMOS program version 21. The result shows (1) Therole of extension on independent small holder farmer of oil palm activity in Mandau Sub District is categorized enough. (2)The empowerment of independent small holder farmers of oil palm in Mandau Sub District is categorized enough. (3) The purpose of extension has worked in Mandau Sub District is categorized reach. (4)the role of extensionhas proven positifly influence and significant toward farmer’s empowerment and the farmer’s empowerment has proven positifly influence and significant toward reach of the extension purposes. Key words: The roleof extension, empowerments, the purpose of extension, independent small holder, oil palm